BP and the Gulf Oil Spill (A) - Marques, Dan; Kim, Jonathan; Mikols, John; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On April 20, 2010 an explosion on board the Deepwater Horizon offshore oil-drilling platform killed 11 workers, injured 17 and triggered a leak that spilled more than 206 million gallons of oil over 665 miles of coastline and 4,000 square miles of fishing waters. This case discusses the events that led to the disaster and oil spill in the Gulf of Mexico. It also outlines key figures within BP's organization and how they factored into the long and difficult corporate communications process.
Originally published in Marques, D., Kim, J., Mikols, J., & ORourke, J. S. (2011). BP and the Gulf oil spill (A). 11-04 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; BP New Zealand (Firm); Organizational behavior; Communication in management; Oil spills -- Mexico, Gulf of